2019
DOI: 10.1021/acsami.9b02511
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Electrocatalytic Nitrogen Reduction Enabled by Confinement of Nanosized Au Particles onto a Two-Dimensional Ti3C2 Substrate

Abstract: A N2 fixation by the electrocatalytic nitrogen reduction reaction from humidified air is regarded to be a critical tool for producing NH3 and reducing the globally accelerating CO2 emissions. Notwithstanding great efforts to improve catalyst activity and selectivity, promoting catalyst accessibility to high N2 concentrations to ensure that active sites fulfill their function should be a promising design direction. Here, Au nanoparticles are firmly anchored through atomic O on the surface of two-dimensional Ti3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…To further enhance the NRR activity, gold particles were anchored on 2-D Ti 3 C 2 substrate via atomic O. Herein, Au-Ti 3 C 2 acts as web which effectively adsorb N 2 and effectively N 2 was activated by low energy barrier. [43] As a result, it has manifested efficiency as high as 18.34% in 0.1 m HCl at −0.2 V with 30.06 µg h −1 mg cat −1 ammonia yield rate. Similarly, titanium oxynitride containing high oxygen content was explored as NRR catalyst by Zhang and co-workers.…”
Section: (5 Of 44)mentioning
confidence: 97%
“…To further enhance the NRR activity, gold particles were anchored on 2-D Ti 3 C 2 substrate via atomic O. Herein, Au-Ti 3 C 2 acts as web which effectively adsorb N 2 and effectively N 2 was activated by low energy barrier. [43] As a result, it has manifested efficiency as high as 18.34% in 0.1 m HCl at −0.2 V with 30.06 µg h −1 mg cat −1 ammonia yield rate. Similarly, titanium oxynitride containing high oxygen content was explored as NRR catalyst by Zhang and co-workers.…”
Section: (5 Of 44)mentioning
confidence: 97%
“…Besides, Cheng et al [22] also found that a single Mo atom immobilized on 2D Ti 2 NO 2 MXene acts as an electrocatalyst for NRR and exhibits good performance. Liu et al [79] applied nano-sized Au particles onto the surface of 2D Ti 3 C 2 by ultrasonic reduction method, and confirmed that a large amount of N 2 adsorption energy at the interface between high-valence gold clusters and Ti 3 C 2 is the driving force for weakening the NN triple bond. When the Au content of Au/Ti 3 C 2 is 0.94%, the average yield of NH 3 production is 30.06 µg h −1 mg −1 , and the FE is 18.34% at −0.2 V versus RHE.…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 98%
“…Unterminated (bare) MXenes are metallic with a high density of states at the Fermi level. The electronic properties of MXenes are significant depending on the properties of M, X elements and surface terminations [11,19,[55][56][57][58][59]. Upon surface modification, some of the MXenes are tuned from metallic to semiconducting.…”
Section: Electronic Propertymentioning
confidence: 99%